Maladaptive Synaptic Plasticity in L-DOPA-Induced Dyskinesia - Wang, Qiang; Zhang, Wangming (Frontiers in Neural Circuits, 2016)
The emergence of L-DOPA-induced dyskinesia (LID) in patients with Parkinson disease (PD) could be due to maladaptive plasticity of corticostriatal synapses in response to L-DOPA treatment. A series of recent studies has revealed that LID is associated with marked morphological plasticity of striatal dendritic spines, particularly cell type-specific structural plasticity of medium spiny neurons (MSNs) in the striatum. In addition, evidence demonstrating the occurrence of plastic adaptations, including aberrant morphological and functional features, in multiple components of cortico-basal ganglionic circuitry, such as primary motor cortex (M1) and basal ganglia (BG) output nuclei. These adaptations have been implicated in the pathophysiology of LID. Here, we briefly review recent studies that have addressed maladaptive plastic changes within the cortico-BG loop in dyskinetic animal models of PD and patients with PD.